FEATURES OF DECISION-MAKING IN TRANSPORT SYSTEMS, IN THE PRESENCE OF A LARGE AMOUNT OF INFORMATION AND RESOURCES OF THE INTERNET - Киркин, Александр (SWorldJournal, 2020)
This paper considers the topical issue of searching for remote information resources, for making optimal decisions at different time intervals, and a significant geographical distance of all possible elements of the transport process. In view of the impo